Correlação entre fatores bucais de para-atletas e o pH salivar - Morodome, Fernanda (2021)
This study aimed to investigate the association of the salivary pH and parameters of oral health in Brazilian para-athletes. The sample was composed of 271 Brazilian para-athletes (147 athletics, 61 powerlifting, and 63 swimming (mean age was 31.2, ± 11.7 years). Data collected during anamnesis, clinical examination, and saliva collection revealed that salivary pH was different among sports (p=0.01) and tends to decrease as age and body mass index increase (p= 0.026; p=0.027, respectively). The mean decay missing filled teeth was 8.8 (± 0.57) but there is no correlation with salivary pH (R2= -0.0852; CI 95%, -0.215 to 0.047; p= 0.194) as habits of grinding, clenching teeth or bruxism was not associated with salivary pH (p=0.317; 0.932 and 0.444, respectively). Regarding breathing, para-athletes that have buccal breathing had significantly higher salivary pH (p= 0.04). This data was confirmed by multiple logistic regression (p=0.05). Open bite, lip seal, geographic or fissured tongue also were not associated with variation of salivary pH (p> 0.05). This study provided evidence of an association between salivary pH with age, body mass index, type of breathing, and type of sport practiced by the para-athletes.